2011
DOI: 10.1292/jvms.11-0135
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol-A (BPA) Affects Reproductive Formation across Generations in Mice

Abstract: ABSTRACT. To understand effects of Bisphenol-A (BPA) exposure on the reproductive organ across generations, we analyzed morphology of the uterus and ovary, and the methylation pattern of HOXA10 gene of the 2 nd generation. Pregnant mice (F0) were treated with sc injection of BPA in sesame oil at various doses of 0-1,000 mg/kg Bwt on days 12-16 of gestation. Their offspring (F1) were bred by foster mice, and the offspring (F2) from F1 mice were prepared. That is, F1 mice experienced in utero BPA exposure during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
1
20
0
1
Order By: Relevance
“…However, this study did not control for the estrus cycle stage when the F2 mouse uterine tissue was collected for analysis. Indeed, the data presented indicate large variance in uterine weights in some of the groups (up to 3.7-fold variation; see Table 1 in [100]), consistent with the tissue being harvested at different estrus cycle stages. This study [100] was therefore excluded from further consideration.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…However, this study did not control for the estrus cycle stage when the F2 mouse uterine tissue was collected for analysis. Indeed, the data presented indicate large variance in uterine weights in some of the groups (up to 3.7-fold variation; see Table 1 in [100]), consistent with the tissue being harvested at different estrus cycle stages. This study [100] was therefore excluded from further consideration.…”
Section: Resultssupporting
confidence: 61%
“…In this section we considered all studies that report changes in DNA methylation [56,60,100] and histone modification [57] in uteri of exposed animals. Hox genes are subject to epigenetic regulation [101,102]; therefore we also considered studies that report changes in Hox gene expression [54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In females, perinatal exposure to BPA increased the number of terminal end buds in mammary tissues of CD-1 mice exposed to estradiol later in life without affecting the terminal end buds in mammary tissues of C57BL/6 mice [22]. Furthermore, BPA increased the weight of offspring born to gestationally exposed ICR and adult CD1 Swiss mice, decreased the weight of offspring born to neonatally exposed ICR mice, but did not affect the weight of offspring born to gestationally and neonatally exposed C57BL/6J mice [15,[38][39][40]. Although timing of exposure may also play a role in birth weight following exposure to BPA, future studies should directly compare BPA effects in various strains to account for other potential confounders.…”
Section: Discussionmentioning
confidence: 93%
“…These structures expressed Hoxa10 (homeobox A10), a transcription factor that mediates proliferation of stromal tissue prior to implantation. Two other studies reported that BPA, at both low- and high doses, increased expression of Hoxa10 in prenatally exposed adult CD-1 and ICR mice (Bromer et al 2010; Hiyama et al 2011). …”
Section: Uterine Endometriummentioning
confidence: 96%